Determination of the Primary Excitation Spectra in XPS and AES - Nicolas Pauly; Francisco Yubero; Sven Tougaard (Nanomaterials, 2023)
This paper reviews a procedure that allows for extracting primary photoelectron or Auger electron emissions from homogeneous isotropic samples. It is based on a quantitative dielectric description of the energy losses of swift electrons travelling nearby surfaces in presence of stationary positive charges. The theory behind the modeling of the electron energy losses, implemented in a freely available QUEELS-XPS software package, takes into account intrinsic and extrinsic effects affecting the electron transport. The procedure allows for interpretation of shake-up and multiplet structures on a quantitative basis. We outline the basic theory behind it and illustrate its capabilities with several case examples. Thus, we report on the angular dependence of the intrinsic and extrinsic Al 2s photoelectron emission from aluminum, the shake-up structure of the Ag 3d, Cu 2p, and Ce 3d photoelectron emission from silver, CuO and CeO2, respectively, and the quantification of the two-hole final states contributing to the L3M45M45 Auger electron emission of copper. These examples illustrate the procedure, that can be applied to any homogeneous isotropic material.